A comparative study on perioperative outcomes between robotic versus laparoscopic D2 total gastrectomy. (June 2022) - Li, Zhenshun; Qian, Feng; Zhao, Yongliang; Chen, Jun; Zhang, Fan; Li, Zhengyan; Wang, Xiaosong; Li, Pingang; Liu, Jiajia; Wen, Yan; Feng, Qing; Shi, Yan; et al.
Abstract: Objective: Robotic surgery has been increasingly used worldwide owing to its advanced features. However, the significant benefits of robotic total gastrectomy (RTG) over laparoscopic total gastrectomy (LTG) have yet to be demonstrated. We conducted a prospective cohort study to compare the safety and efficacy of robotic and laparoscopic total gastrectomy (LTG) with D2 lymphadenectomy for AGC. Methods: Between March 26, 2018 and July 30, 2021, 155 patients between 18 and 80 years of age with locally advanced gastric cancer (cT2-4a, N0/+, M0) were enrolled. The perioperative outcomes within 30 days after surgery were compared between the RTG (n = 69) and LTG (n = 73) groups on a per-protocol (PP) basis. Postoperative complications were evaluated according to the Clavien-Dindo classification. Results: The overall postoperative morbidity rate was 21.74% in the RTG group and 28.77% in the LTG group with no significant difference (P = 0.44), RTG was associated with a lower incidence of pneumonia (4.35% vs. 15.07%, P = 0.047). No mortality was observed in either group. There was no significant difference in the total operative time (284.48 vs. 271.73 min, P = 0.171), but RTG was associated with a lower estimated volume of blood loss (110 vs. 150 ml, P < 0.001) and more total retrieved lymph nodes (LNs) (41.36 vs 35.1, P = 0.019), more extraperigastric LNs (14.91 vs. 12.19, P = 0.024) and more LNs in the suprapancreatic areas (14.68 vs. 11.82, P = 0.017). The laboratory data (amylase, inflammatory, Albumin and T lymphocyte levels) of the RTG group were better than those of the LTG group. Conclusion: According to the results of this prospective cohort study, for patients with locally advanced gastric cancer, Robotic surgery has advantages over laparoscopic surgery for radical total gastrectomy with D2 lymphadenectomy performed by well-trained doctors. Highlights: As far as we are concerned, this is first prospective cohort study between robotic total gastrectomy (RTG) and laparoscopic total gastrectomy (LTG) for locally advanced gastric cancer. Our study is the first to use multiple amylase markers (serum amylase, serum starch isozyme, ascites amylase and ascites starch isozyme) as quantitative indicators in the comparison of pancreatic trauma, and the results verified that robotic surgery led to less trauma to the pancreas. In our study, we found that there was no significant difference in the total operative time between RTG and LTG, the results of this differ from those of previous studies. At the same time, RTG was associated with a lower incidence of pneumonia, and more retrieved lymph nodes.